EFFECTIVENESS OF WOOLWICH MASSAGE ON BREAST MILK PRODUCTION BASED ON MATERNAL AND INFANT INDICATORS AMONG POSTPARTUM MOTHERS: A QUASI-EXPERIMENTAL STUDY - Pariqa Annisa; Rina Oktaviana; Sri Putriani Sinaga (Journal of World Future Medicine, Health and Nursing, 2026)
Breast milk production is one of the major determinants of successful exclusive breastfeeding during the early postpartum period. Insufficient milk production often leads to early breastfeeding discontinuation and the introduction of infant formula. This study aimed to determine the effectiveness of Woolwich Massage on breast milk production based on both maternal and infant indicators among postpartum mothers. A quasi-experimental study with a pretest–posttest control group design was conducted at BPM Sasyuni, Kampar Regency, Indonesia, from January to March 2026. Thirty postpartum mothers were recruited using consecutive sampling and equally assigned to an intervention group (n = 15) and a control group (n = 15). Breast milk production was assessed using maternal indicators (breast fullness, breast softening, spontaneous milk leakage, let-down reflex, and absence of breast engorgement) and infant indicators (urination frequency, bowel movement frequency, infant satisfaction, sleep duration, and weight gain). The paired t-test revealed a significant increase in breast milk production scores in the intervention group (mean difference = 5.13 ± 0.99; p < 0.001), while the independent t-test demonstrated significantly greater improvement than the control group (p < 0.001). These findings suggest that Woolwich Massage is an effective, safe, and low-cost non-pharmacological intervention that can be integrated into routine postpartum midwifery care to support successful exclusive breastfeeding.